Gambaran Keberdayaan Perempuan di Desa Wisata Pentingsari berdasarkan Resident Empowerment through Tourism Scale (RETS) - Aristya Tri Rahayu (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2018)
The main focus of this research is to measure whether female residents in Desa Wisata Pentingsari perceive themselves as being empowered by tourism. The measurement is carried out using the concept of Resident Empowerment through Tourism Scale (RETS), formulated by Boley and McGehee (2014). This study will show the mean score on the dimensions of psychological empowerment, social empowerment, and political empowerment. Furthermore, the mean score will be interpreted with a scale of assessment proposed by Umar (1998). A questionnaire was distributed to 100 women in Pentingsari Tourism Village who are at productive age between 15 - 64 years old. The result shows that the women in Pentingsari Tourism Village perceived themselves to be more psychologically empowered than socially or politically. On the psychological empowerment, the mean score shows a very high score of 4.26. Meanwhile, on the dimension of social empowerment, the mean score shows a high category of 4.19 and on the dimension of political empowerment 3.69, still in the category high score.